Tea time, March 2005 - O'Neill, Ward, 1951- (2005)
Tony Windsor walking with a wheelbarrow full of papers towards a sign that reads "The Senate Finance and Administration Commission is in Session". John Anderson is having a cup of tea behind a bunker, while several papers have been put on to the fire under the teapot.
Title from acquisitions documentation, see file NLA03/1461.
Part of: Ward O'Neill collection.
Inscriptions: "SMH News Review - Alan Ramsey Column. SMH 24-3-95 for 26-3-95"--In pencil below image; Signed lower right.
Condition: Soiled.
Published in the Sydney Morning Herald on 26 March 2005, in Alan Ramsey's column.
Keywords: Anderson, John, -- 1956- -- Caricatures and cartoons; Windsor, Tony -- Caricatures and cartoons; Politicians -- Australia -- Caricatures and cartoons; Australia -- Politics and government -- 2001- -- Caricatures and cartoons; Federal politicians